LEADERSHIP THAT INSPIRES IN THE CORPORATE ENVIRONMENT: CHARISMA, EMOTIONAL INTELLIGENCE, AND ORGANIZATIONAL CULTURE AS DEVELOPABLE COMPETENCIES - Fritz, Monika (Seven Editora, 2026)
This chapter analyzes the role of charisma in contemporary corporate leadership, integrating it with Emotional Intelligence (EI) as a foundation for authentic, ethical, and culturally sustainable influence. In organizational contexts marked by volatility, pressure for results, and competition for talent, charisma is reinterpreted not as a mystical trait, but as a relational, observable, and trainable competency. Methodologically, this is a narrative bibliographic review that articulates the classical Weberian perspective on charismatic domination, behavioral indicators of charismatic leadership (House, 1977), and contemporary approaches to Emotional Intelligence (Salovey & Mayer, 1990; Goleman, 1995) and organizational purpose (Sinek, 2018). A conceptual model is proposed in which Emotional Intelligence (self-awareness, self-regulation, empathy, and social skills) acts as an antecedent of charismatic behaviors (authentic communication, presence, human connection, and inspiring vision), generating positive effects on trust, engagement, psychological safety, and organizational culture. As a practical contribution, structured development actions applicable to managerial contexts are presented, including self-knowledge, active listening, storytelling, constructive feedback, and mentoring and coaching practices. It is concluded that charismatic leadership, when grounded in emotional competence and ethical responsibility, amplifies organizational results and strengthens collective bonds, fostering collaborative, resilient, and purpose-driven environments.DOI: https://doi.org/10.56238/sevened2026.008-059